Cognitive Limitations and Decision Making - Chariri, Anies (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 1999)
It is widely known that judgment is an inevitable aspect of living for both individuals and organisations. Judgments involve information acquisition and processing that are required in helping individuals make a decision. Individual's ability to search for and process information will eventually determine the accuracy of judgments and decisions made. Unfortunately, individuals, as human beings, have cognitive limitations in searching for and processing information. As a result, they can make an inaccurate judgment. As Hogarth (1980) argues, although individuals are adaptive, they have limited information processing capacities. This paper discusses cognitive limitations of individuals in obtaining and processing information, the potential impact of the limitations on making decisions, and possibilities to overcome the limitations.